THE ROLE OF INFORMATION TECHNOLOGY IN ONLINE LEARNING DURING THE COVID-19 PANDEMIC OF UPT SDN 1 MARGAKAYA: indonesia - Eka Julianti; Ulfa Umurohmi; Abdul Hamid; Salamun (Al-Ibda: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
AbstractCovid-19 Pandemic was greaty impact on education in Indonesia. The learning process which was performed at the school but now learning do from home with online learning. Using of information technology is very helpful on learning process in the Covid-19 virus. Online based learning used in this study is learning that utilizes the use of Whatsapp in information communication tools. However, there are some obstacles in he process of implementing learning at UPT SDN 1 Margakaya such as not all students can take part in the online learning process because of the weak internet network and not all guardians of students have handphone andenthusiastic in participating in the online based learning process. This research was conducted to determine the role of information technology in online learning during Covid-19 Pandemic of UPT SDN 1 Margakaya. This research method uses qualitative methods with a descriptive approach. The result of this research is that the whatsapp application based learning has an important role in the implementation of learning, the other than that there are factors that greatly influence the learning process when carried out online during the Covid-19 Pandemic.Keywords : Covid-19 Pandemic, Online learning, Information Technology